Reduction in skeletal muscle fibrosis of spontaneously hypertensive rats after laceration by microRNA targeting angiotensin II receptor - Stilhano, Roberta Sessa (PLoS One, 2017)
Regeneration of injured skeletal muscles is affected by fibrosis, which can be improved by the administration of angiotensin II (AngII) receptor (ATR) blockers in normotensive animals. However, the role of ATR in skeletal muscle fibrosis in hypertensive organisms has not been investigated yet. The tibialis anterior (TA) muscle of spontaneously hypertensive (SHR) and Wistar rats (WR) were lacerated and a lentivector encoding a microRNA targeting AngII receptor type 1 (At1) (Lv-mirAT1a) or control (Lv-mirCTL) was injected. The TA muscles were collected after 30 days to evaluate fibrosis by histology and gene expression by real-time quantitative PCR (RT-qPCR) and Western blot. SHR’s myoblasts were analyzed by RT-qPCR, 48 h after transduction. In the SHR’s TA, AT1 protein expression was 23.5-fold higher than in WR without injury, but no difference was observed in the angiotensin II receptor type 2 (AT2) protein expression. TA laceration followed by suture (LS) produced fibrosis in the SHR (23.3±8.5%) and WR (7.9±1.5%). Lv-mirAT1 treatment decreased At1 gene expression in 50% and reduced fibrosis to 7% 30 days after. RT-qPCR showed that reduction in At1 expression is due to downregulation of the At1a but not of the At1b. RT-qPCR of myoblasts from SHR transduced with Lv-mirAT1a showed downregulation of the Tgf-b1, Tgf-b2, Smad3, Col1a1, and Col3a1 genes by mirAT1a. In vivo and in vitro studies indicate that hypertension overproduces skeletal muscle fibrosis, and AngII-AT1a signaling is the main pathway of fibrosis in SHR. Moreover, muscle fibrosis can be treated specifically by in loco injection of Lv-mirAT1a without affecting other organs.